Penelitian Grounded Theory: Pengertian, Prinsip-Prinsip, Metode Pengumpulan Dan Analisis Data. - Ruslan R; Umi Nur Khalifatun; Ulfiani Rahman (Edu Sociata : Jurnal Pendidikan Sosiologi, 2023)
Grounded research has developed very rapidly in recent years, from what was originally in the field of sociology it has expanded to other fields. Grounded Theory research is a qualitative research design that allows researchers to form constructs and build theories from data directly collected by researchers rather than from existing theories. Grounded theory is a reflexive and open approach, where data collection, data development, theoretical concept development, and literature review take place in a cyclical (continuous) process. The stages of grounded theory research occur simultaneously. Researchers observe, collect and organize data and form theories from the data at the same time. One of the important techniques in grounded theory research is a constant comparison process where each data is compared with all other data one by one. Data can be collected through interviews, observation, recording, or a combination of these methods. In grounded theory, there is great emphasis on exploring ongoing behavioral data (life history) to see the process and is aimed at capturing things that are causal in nature. Next, the data was analyzed using coding and theoretical sampling procedures. The procedure carried out in the data analysis stage which is the basis of the coding process is to carry out continuous comparisons and ask questions. The grounded theory research method emphasizes data validity through verification and using coding as the main tool for data processing. Finally, after the theory is generated with the help of interpretive procedures, the research is written up and presented. The quality of grounded theory research is largely determined by the steps that are carried out well, correctly and in a disciplined manner.